2021
DOI: 10.1111/1346-8138.16072
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the unmet needs among psoriasis patients in the Asia‐Pacific region

Abstract: Studies on the psychosocial and emotional burden of psoriasis have been extensive; however, there is limited knowledge and awareness of patients’ attitude and behavior towards psoriasis treatment. To understand psoriasis patients’ attitude and behavior towards treatment of psoriasis, especially those treated with biologics, a multi‐stage study qualitative and quantitative methodology was conducted among psoriasis patients. An online survey was conducted with 45 moderate‐to‐severe psoriasis patients each in Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Psoriasis affects 2–4% of the adult population in Western countries, with a worldwide prevalence ranging from 0.91% to 8.5% [ 1 3 ]. Estimated prevalence of psoriasis is 2.3–6.6% in Australia, 0.24% in Taiwan and 0.45% in South Korea [ 4 ]. In Middle East countries such as Egypt, Lebanon, Saudi Arabia and United Arab Emirates, the estimated prevalence of psoriasis in the overall population ranges from 0.40% to 0.58% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis affects 2–4% of the adult population in Western countries, with a worldwide prevalence ranging from 0.91% to 8.5% [ 1 3 ]. Estimated prevalence of psoriasis is 2.3–6.6% in Australia, 0.24% in Taiwan and 0.45% in South Korea [ 4 ]. In Middle East countries such as Egypt, Lebanon, Saudi Arabia and United Arab Emirates, the estimated prevalence of psoriasis in the overall population ranges from 0.40% to 0.58% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey study showed that the top treatment needs of patients with psoriasis in the Asia-Pacific region were long-term remission and reduced recurrence. In this region, 68% of patients with psoriasis believe that the rapid clearance of skin lesions is the key to psoriasis treatment options ( 71 ). Similarly, the 2018 edition of the Chinese Psoriasis Diagnosis and Treatment Guidelines considers the prevention of recurrence as an important goal of psoriasis treatment and emphasizes that reducing disease progression and recurrence and improving quality of life are crucial for patients ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…The residual minimal disease can still substantially impact HR‐QOL 38 . The extent of this psychological distress is often under‐recognised 39 and far‐reaching 40 . Relying only on PASI could therefore result in misalignment between physician‐reported and patient‐reported severity.…”
Section: Discussionmentioning
confidence: 99%
“…38 The extent of this psychological distress is often under-recognised 39 and far-reaching. 40 Relying only on PASI could therefore result in misalignment between physician-reported and patient-reported severity. Australian data highlights the importance of addressing the spectrum of physical and psychological manifestations associated with psoriasis.…”
Section: Consideration Of Other Assessment Metricsmentioning
confidence: 99%